2022
DOI: 10.3389/fvets.2022.987667
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of PRRS and genetic variation analysis of the ORF5 gene in Shandong Province, 2020–2021

Abstract: Since the rise of porcine reproductive and respiratory syndrome virus (PRRSV) in China, mutations have occurred regularly. In particular, the emergence of HP-PRRSV has significantly improved the pathogenicity of PRRSV. It has brought huge economic losses to the Chinese pig farming industry. To understand the current prevalence and evolution of PRRSV in Shandong Province, 1,344 samples suspected of having PRRSV were collected from local hog farms of different sizes. Genetic variation in the isolated PRRSV ORF5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…One crucial pillar of disease control is the genetic characterization of circulating virus strains in order to identify the origin of infection and determine the routes of transmission between pig farms, within a geographical region or an administrative area. Sequencing one of the most variable genomic regions, the ORF5, is still a gold-standard procedure for surveying these issues [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The information obtained by means of molecular epidemiology further assists the improvement of external disease control measures of a given pig herd and provides the basis for reliable production of animal goods.…”
Section: Discussionmentioning
confidence: 99%
“…One crucial pillar of disease control is the genetic characterization of circulating virus strains in order to identify the origin of infection and determine the routes of transmission between pig farms, within a geographical region or an administrative area. Sequencing one of the most variable genomic regions, the ORF5, is still a gold-standard procedure for surveying these issues [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The information obtained by means of molecular epidemiology further assists the improvement of external disease control measures of a given pig herd and provides the basis for reliable production of animal goods.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 45 strains had mutations in the neutralization epitope region, including strains from lineages 1, 3, and 8, as well as one strain had a mutation in lineage 5. Mutations in the neutralization epitope region of the virus can result in immune evasion, thus reducing the protective efficacy of the vaccine ( Li et al, 2022 ). Glycosylation of the GP5 is the primary mechanism of virus immune escape and persistent infection, leading to a decrease in the body’s immunity and antibody production ability ( Ansari et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…The analysis revealed that the major parental strain belonged to lineage 1, while the minor parental strain belonged to lineage 8, indicating that recombination between lineage 8 and lineage 1 strains was prevalent. In addition, Li et al (2022) also conducted a recombination analysis based on the ORF5 gene, and RDP identified four recombination events, with both the major and minor parental strains belonging to lineage 1. Recombination is a significant driving force in the evolution of PRRSV, allowing the virus to adapt to environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…China are the live attenuated JE vaccine (SA-14-14-2) and inactivated JE vaccine (P3) [27,28]. Shandong, Zhejiang and Guangdong Provinces included the JE vaccine in their childhood immunization programs beginning in 2004, 1986, and 1986, respectively [29][30][31]. Children aged 8 and 24 months can receive two free doses of the live attenuated vaccine in these areas.…”
Section: Je Is a Vaccine-preventable Disease The Vaccines Currently I...mentioning
confidence: 99%